Ganglioneuroblastoma in a newborn with multiple metastases: a case report - Eva Gauchan (Journal of Medical Case Reports, 2017)
Abstract Background Ganglioneuroblastoma is a tumor of peripheral neuroblastic tissue which occurs predominantly in the pediatric age group; it is a rare occurrence in the newborn period with only one case reported at birth to date. Case presentation We report the case of a newborn male baby of Brahmin ethnicity from Nepal who presented with respiratory distress and blueberry muffin skin lesions after birth. A computed tomography scan showed a mass lesion in the posterior mediastinum, which was diagnosed as ganglioneuroblastoma on fine-needle aspiration cytology. He also had metastases to multiple sites including heart, lungs, skin and brain. Conclusions Ganglioneuroblastoma is a rare tumor in newborns. Any newborn presenting with respiratory distress associated with blueberry muffin skin lesions should be evaluated for neuroblastic tumor.